Odpowiedzi

2010-01-24T10:50:06+01:00
1) 2x-y=4
x+y=11 /*(-2)

2x-y=4
-2x-2y=-22

-3y=-18 /:(-3)
y=6

x+y=11
x+6=11
x=11-6
x=5


2) x-2y=-3 /*(-2)
2x+3y=8

-2x-4y=6
-2x+3y=8

-y= 14 /*(-1)
y=-14

x-2y=-3
x-2*(-14)=-3
x+28=-3
x=-3-28
x=-31
Najlepsza Odpowiedź!
2010-01-24T10:52:49+01:00
1) 2x-y=4
{
x+y=11
dodajemy stronami
2x - y + x + y = 4 + 11
3x = 15x
x = 5
2x - y = 4
10 - y = 4
-y = 4 - 10
-y = -6
y = 6
odp
x = 5
y = 6
2) x-2y=-3
{
2x+3y=8
obliczamy x z pierwszego równania
x - 2y = -3
x = -3 + 2y
wstawiamy do drugiego równania
2(2y - 3) + 3y = 8
4y - 6 + 3y = 8
7y = 8 + 6
7y = 14
y = 2
x - 2y = -3
x - 4 = -3
x = -3 + 4
x = 1
odp
x = 1
y = 2